Enhanced performance of lithium-ion battery cathodes using a composite conductive network of CNTs, GQDs, and GNRs embedded in Li1.2Mn0. 54Ni0.13Co0.13O2 (LMNCO) - Latif, Hamid; Sabah, Noor Us; Sattar, Abdul; Öktem, Ahmet Sinan; Uyanik, Mehmet Sinan; Topac, Erdal; Anjum, Dalaver H. (Elsevier, 2025)
Lithium-rich Li-ion battery cathode materials are known for their high specific capacities and working potential. However, their practical application is limited by the significant decline in discharge potential and capacity during repeated cycling. In this study, we introduce a highly conductive electrode architecture, encapsulating within carbon nanotubes (CNTs), graphene nano-ribbons (GNRs) and graphene quantum dots (GQDs) to mitigate rapid capacity fading and suppress voltage decay. Three Li1.2Mn0. 54Ni0.13Co0.13O2 cathode materials were synthesized. The first sample, pristine Li1.2Mn0. 54Ni0.13Co0.13O2, was synthesized using a nitrate co- precipitation method. The second cathode, GNRs-CNTs@Li1.2Mn0. 54Ni0.13Co0.13O2, incorporates a mixture of carbon nanotubes and graphene nanoribbons. The third cathode, GQDs:GNRs-CNTs@Li1.2Mn0. 54Ni0.13Co0.13O2), further integrates graphene quantum dots within the graphene nanoribbons and carbon nanotubes matrix. The inclusion of highly conductive GNRs-CNTs and GQDs effectively enhances the electrical conductivity of Li1.2Mn0. 54Ni0.13Co0.13O2, increasing the specific capacity from 246.95 to 316.94 mAhg(-1). Additionally, GQDs prevent side reactions and surface phase transitions, thereby improving thermal stability.
Keywords: Li-ion batteries; Graphene nano-ribbons; Graphene quantum dots